Moderating effects of national culture on the psychological contract breach and outcome relationship: a meta-analysis. Issue 3 (12th February 2021) - Jayaweera, A. Thushel; Bal, Matthijs; Chudzikowski, Katharina; de Jong, Simon
Abstract : Purpose: This paper contains a meta-analysis of the psychological contract literature published in the last two decades. The aim of this paper was to investigate the moderating role of national culture in the individual-level relationships between psychological contract breach (PCB) and two important work outcomes, namely job performance (in-role and organizational citizenship behaviors) and turnover (actual and intended). Design/methodology/approach: After an extensive literature search, 134 studies were found which matched the authors' aim. The authors then incorporated national cultural scores based on the GLOBE study to include country-level scores to identify how the PCB relationships with these four outcomes vary across cultures. Findings: The findings indicate that national cultural practices moderated the associations between PCB and the four outcomes, yet, no significant moderations for uncertainty avoidance practices. Originality/value: While existing research has examined the impact of the breach on work outcomes such as job performance and turnover, there are few empirical studies that examine how national cultural practices influence the relationships between psychological contract breach and job performance and turnover. The authors address this need by investigating and creating a deeper insight into how cultural practices such as institutional collectivism, performance-orientation, power-distance, future orientation and gender egalitarianism moderate the relationships between PCB and job performance and turnover.